Sexual medicine education in Finland – Opinions of general practitioners, medical students, and midwifery students on their sexual medicine competence and education - Manninen, Sanna-Mari (fi=Turun yliopisto|en=University of Turku|, 2024)
Sexual problems are common, and the likelihood of experiencing them increases with age and various chronic diseases. Therefore, healthcare professionals should be able to bring up sexual issues with their patients. The present thesis aimed to evaluate the barriers experienced by Finnish general practitioners (GPs) and final-year medical students and midwifery students to bringing up sexual issues with their patients. Further, it set out to determine GPs’ self-reported inquiries about sexual problems when dealing with patients with chronic diseases as well as GPs’ awareness of medications inducing sexual problems. Additionally, it assesses the knowledge of and educational interest in sexual medicine of medical and midwifery students. The study of GPs collected data from a random sample of 1,000 Finnish GPs. For the study of students, all final-year medical and midwifery students graduating between December 2018 and May 2019 in Finland were enrolled. Web-based questionnaires were utilized. Although the GPs and both the medical and midwifery students reported a good competence in discussing sexual issues with patients, several barriers emerged that hindered them from bringing up such issues in patient encounters. In addition, the majority of the GPs considered that sexual problems are often side effects of medications prescribed for other pathologies. Nevertheless, the GPs self-reported that they seldom followed up on whether the medications, once prescribed, caused side effects in sexual functions. The majority of the GPs reported that the sexual medicine education they had received in medical school was insufficient. The midwifery and, in particular, the medical students reported a lack of knowledge in several fields of sexual medicine. Additionally, the majority of medical students and approximately half the midwifery students reported receiving too little sexual medicine education during their studies. The results of the present thesis highlight the importance of increasing sexual medicine education in both medical and midwifery education.

Seksuaalilääketieteen opetus Suomessa - Terveyskeskuslääkärien, lääketieteen opiskelijoiden ja kätilöopiskelijoiden mielipiteitä seksuaalilääketieteellisestä osaamisestaan ja opetuksesta Seksuaaliongelmat ovat yleisiä ja niiden esiintyvyys kasvaa ikääntyessä sekä erilaisten kroonisten sairauksien myötä. Sen vuoksi on tärkeää, että terveydenhuollon ammattilaiset osaavat ottaa seksuaaliasiat puheeksi potilastilanteissa. Tässä väitöskirjatutkimuksessa selvitettiin, mitkä tekijät estävät suomalaisia terveyskeskuslääkäreitä sekä viimeisen vuoden lääketieteen opiskelijoita ja kätilöopiskelijoita ottamasta seksuaaliasioita puheeksi potilaidensa kanssa. Lisäksi selvitettiin terveyskeskuslääkärien tietoisuutta kroonisten sairauksien ja niiden lääkitysten aiheuttamista seksuaaliongelmista ja sitä, kartoittavatko he mahdollisia seksuaaliongelmia potilailta, joilla on jokin krooninen sairaus. Edelleen selvitettiin lääketieteen opiskelijoiden ja kätilöopiskelijoiden tietämystä ja kiinnostusta seksuaalilääketiedettä kohtaan. Aineisto kerättiin satunnaisotannalla valitulta tuhannelta suomalaiselta terveyskeskuslääkäriltä sekä kaikilta joulukuun 2018 ja toukokuun 2019 välisenä aikana Suomessa valmistuneilta lääketieteen opiskelijoilta ja kätilöopiskelijoilta. Käytössä oli sähköinen kyselylomake. Sekä terveyskeskuslääkärit että lääketieteen opiskelijat ja kätilöopiskelijat raportoivat, että heillä on hyvä osaaminen koskien seksuaaliasioista keskustelemista. Esiin nousi kuitenkin useita seksuaaliasioiden puheeksi ottamisen esteitä. Kroonisten sairauksien ja seksuaaliongelmien yhteyksien tutkimuksessa, suurin osa terveyskeskuslääkäreistä piti seksuaaliongelmia usein muihin sairauksiin määrättyjen lääkkeiden sivuvaikutuksina. Siitä huolimatta vain harvat raportoivat kysyvänsä mahdollisia lääkitysten sivuvaikutuksina ilmenneitä seksuaaliongelmia. Suurin osa terveyskeskuslääkäreistä koki opintojensa aikana saamansa seksuaalilääketieteen opetuksen riittämättömäksi. Sekä lääketieteen opiskelijat että kätilöopiskelijat raportoivat tiedon puutetta useilla seksuaalilääketieteen osa-alueilla. Lisäksi suurin osa lääketieteen opiskelijoista ja noin puolet kätilöopiskelijoista koki saaneensa liian vähän seksuaalilääketieteen opetusta. Tämän väitöskirjatutkimuksen tulokset korostavat seksuaalilääketieteen opetuksen lisäämisen tärkeyttä niin lääketieteen kuin kätilöopinnoissakin.